Cardiac papillary fibroelastomas: A 10-year single-center surgical experience and long-term echocardiographic follow-up study - Kolek, Martin; Dvorackova, Jana; Motyka, Oldrich; Brat, Radim (Biomedical papers, 2020)
Aims: Limited contemporary data are available on the clinical and echocardiographic outcomes after surgery for cardiac papillary fibroelastoma (CPF). The aim of this study was to review the clinical manifestations, pathological characteristics, surgical management, and prognoses of patients with histologically verified CPF, who underwent surgery at our cardiac surgery center from 2008 to 2018. Methods and Results: Twelve patients of median age 62 years (28 to 77 years) were treated. Embolic stroke or transient ischemic attack (five patients, 42%) were the only CPF clinical manifestations. Eleven (92%) tumors were localized on the valves, with the aortic valve being the most common tumor site (seven patients; 58%). Multiple factor analysis revealed no independent predictor of CPF-related embolization. Simple shave tumor excision was sufficient in most patients (10 patients, 83%). No operative or tumor-related late mortality during the median follow-up period of 4.7 years (1.1 to 10.2 years) was recorded. Asymptomatic metachronous valve tumor recurrence (in a location different from that of the original tumor) was revealed in two patients (17%) by transesophageal echocardiography (TEE), not detected by transthoracic echocardiography (TTE). One of these two patients underwent repeated surgery for CPF but later suffered a recurrent embolic stroke, due to another tumor recurrence. Conclusion: CPF can be safely and effectively treated surgically. TEE is superior to the TTE option in CPF post-operative recurrence detection. There is a clear need for a prospective study to determine criteria for embolization risk stratification and optimum management in patients with CPF.
Keywords: cardiac papillary fibroelastoma; embolism; stroke; echocardiography; cardiac surgical procedures